The Council of Nicaea: A Reading from Indigenous Women's Perspective - Longkumer, Atola (International review of mission, 2025)
The experience of Indigenous women in the church is marked by exclusion even though Indigenous women are often the most active participants in the faith. “Living the Apostolic Faith Today” with a commitment to the decolonization of Christian mission cannot be complete without dismantling exclusive theologies and practices rooted in historical circumstances. With an objective to call on the church to conscientiously and consciously include Indigenous women in the walk toward visible unity, this article will be guided by two questions. First, what lessons can be learned from the historical circumstances of the Council of Nicaea in addressing conflicts and consequences of conflicts that marginalize vulnerable people like Indigenous women? Second, how do the outcomes of the Council of Nicaea, such as “orthodoxy,” simultaneously exclude and inform faith practices today?